Age-Dependent Loss of Sirtuin1 (Sirt1) Correlates with Reduced Autophagy in Type 2 Diabetic Patients (T2DM) - Fischer, Julia; Hos, Nina Judith; Tritschler, Sophie; Schmitz-Peters, Joel; Ganesan, Raja; Calabrese, Chiara; Schiller, Petra; Brunnert, Hannah; Nowag, Angela; Winter, Sandra; Hanßen, Ruth; Römer, Katja; et al. (Diabetology, 2025)
Aims and Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder frequently associated with increased inflammation and dysregulated innate immune responses. Thus, patients with T2DM are predisposed to bacterial infections. However, the underlying mechanism is poorly understood. The NAD+-dependent deacetylase Sirtuin1 (SIRT1) plays an important role in regulating cellular metabolism, including T2DM and aging. Furthermore, we have recently demonstrated that SIRT1 critically regulates inflammatory pathways and autophagy during infection. Thus, we aimed to investigate SIRT1 expression and its correlation with autophagy in peripheral blood mononuclear cells (PBMCs) from patients with T2DM compared to non-diabetic patients. Methods: Clinical characteristics of the study subjects were obtained. SIRT1 and autophagic markers such as p62 and LC3-I/II were determined using Western blot analysis followed by densitometric analysis. Results: We found that SIRT1 levels were decreased in PBMCs of diabetic patients in an age-dependent manner. Importantly, reduced SIRT1 expression correlated with reduced LC3-II/I ratios, indicating reduced autophagy. Reduced SIRT1 also corresponded to decreased autophagic adaptor protein Sequestome-1/p62. Conclusions: In summary, our results suggest a potential role of SIRT1 in regulating autophagy in PBMCs from T2DM patients.